2012
DOI: 10.2147/lra.s16314
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Tenon's anesthesia: an update

Abstract: Sub-Tenon’s block has become the most common technique of orbital regional anesthesia in many centers. It provides effective anesthesia to the orbit with a lower incidence of sight-threatening complications than sharp needle techniques. This article will discuss the relevant anatomy, finer points of sub-Tenon’s block technique, and the evidence supporting its safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 77 publications
(80 reference statements)
1
31
0
Order By: Relevance
“…A good understanding of the anatomical landmarks and attention to the appropriate technique is essential to achieve the acquired akinesia, mydriasis, and desensitization of cornea, iris, and sclera (Fig. ) …”
Section: Introductionsupporting
confidence: 93%
“…A good understanding of the anatomical landmarks and attention to the appropriate technique is essential to achieve the acquired akinesia, mydriasis, and desensitization of cornea, iris, and sclera (Fig. ) …”
Section: Introductionsupporting
confidence: 93%
“…This technique is well known as a useful method of inducing ocular anesthesia. 79 Wollensak 10 has described previously the use of a sT injection using glyceraldehyde (a chemical crosslinking agent similar in concept to the FARs described in this study) to stiffen the rabbit sclera 10 and genipin has been shown to limit axial length in FD guinea pigs. 11,12 These investigators have demonstrated an advantage of using a soluble chemical agent over the photochemical (CXL) technique.…”
mentioning
confidence: 99%
“…The extent of the sub-Tenon's space, as defined by Tenon's capsule (or orbital fascia), limits the area of cross-linking to this space, favoring uniform distribution across the posterior sclera, which is the location of desired effect. 14 Thus, in lieu of such concerns and potential benefits, the development of an alternative cross-linking approach that could avoid the use of UV-A light, and avoid epithelial removal (for the cornea), is less cytotoxic and could provide crosslinking to the posterior sclera without requiring a light source, and could be of significant interest to the field of ophthalmic therapeutics. This has prompted a search for candidate chemical cross-linking agents that could be used for therapeutic stabilization of either the cornea and/or sclera.…”
Section: Resultsmentioning
confidence: 99%